Flexural Behaviour of Precast Lightweight Concrete Sandwich Slabs With Demountable Bolted Steel Shear Connectors - Al-Kerwei, Rana H.; Osman, S. A.; Al-Zand, Ahmed W.; Hanoon, Ammar N. (Civil Engineering Journal, 2025)
A concrete slab is a fundamental element and contributes the highest weight in structural buildings. In this paper, a new type of sandwich slab consisting of two layers of lightweight concrete and demountable steel connectors is proposed in a new attempt to reduce the weight of the floors within the structure and apply a simpler and faster approach to connecting the layers of sandwich panels. The structural effects of the proposed connectors on Precast Lightweight Concrete Sandwich Slab (PLCSS) are evaluated experimentally and theoretically in terms of strength, stiffness, degree of composite action, and usability for floor construction. The behaviors of six PLCSS specimens subjected to four-point loads were investigated, studying the effects of varied parameters such as different numbers, arrangements, and shapes of demountable steel connectors (I, V, and X connector shapes) fastened with steel bolts, in addition to one solid concrete slab as a reference specimen. The panels' performance in this structural system was evaluated by measuring the degree of composite action using load, displacement, stress, and neutral axis methods. Based on the experimental results, the slab panels exhibited composite panel behavior until the point of failure. Under flexural loads, the panel behaved similarly to that of a solid one-way slab; crack patterns appeared in one direction. The specimens with IC, VC, and XC showed different load capacity values, ranging from 22.74 kN to 50.55 kN; these values depend on the types of shear connectors and their numbers in the sandwich panels. Using V and X connectors enhances the composite action between layers, increasing the shear demand and making the shear failure more likely. It can be concluded that demountable shear connectors can transfer shear between the two concrete wythes, resulting in a composite panel with structural integrity, a lighter weight, and satisfying ACI specifications for floor applications. Doi: 10.28991/CEJ-2025-011-02-06 Full Text: PDF